A Semiotic Analysis Of Collagen Milk Advertising Using Roland Barthes’ Theory - Ellin Nurhayati; Rachel Putri Andra; Fransisca Indah Sulistyowati; Mayang Pipit (International journal of technology and education research, 2026)
The purpose of this study is to apply Roland Barthes' semiotic theory to examine the meanings created in the Collagena Milk commercial. The study uses a qualitative descriptive approach, gathering information from a YouTube Collagena Milk commercial starring Song Hye Kyo. Three layers of signification denotation, connotation, and myth are the main emphasis of the investigation. The results show that the advertisement's verbal and visual components such as the celebrity endorser, product packaging, scientific drawings, and promotional messages are presented at the denotative level. Connotative connotations associated with youth, beauty, health, self-assurance, reliability, and ideal femininity are produced by these indicators. At the mythological level, the commercial promotes the idea that using collagen-based treatments may preserve beauty and that young appearance is the ideal standard of beauty. The inclusion of scientific images and celebrity endorsements enhances the sense of the efficacy and legitimacy of the product. The study comes to the conclusion that the commercial can serve as a cultural text that influences societal views of beauty, age, and femininity in addition to being a marketing tool due to the interplay of denotative, connotative, and mythological connotations. The results advance knowledge of how advertising uses verbal and visual cues to create and uphold cultural beliefs.